PENGGUNAAN AKUN BERBASIS OTOMATIS DI TWITTER/X SEBAGAI PLATFORM TANYA JAWAB SOSIAL - Widiatmika, Keyza Pratama (Jurnal Sosial Humaniora, 2024)
Twitter/X has pioneered a new communication landscape through the introduction of auto-based accounts. In Indonesia, these accounts, commonly known as 'Menfess,' enable users to share anonymous messages on various topics. A significant feature of these accounts is their role in Social Q&A, acting as a platform for questioning and seeking information. This study aims to investigate how Indonesians utilize auto-based accounts for Social Q&A interactions. To achieve this goal, a qualitative approach was employed, involving in-depth interviews with 10 Indonesian youths aged between 18 and 25 years. The findings reveal that these accounts have evolved from mere channels for anonymous confessions to sophisticated forums for engagement and knowledge sharing, particularly among users discussing sensitive topics. A key observation is the strategic use of auto-based accounts, which not only broadens user perspectives but also amplifies their confidence. However, it is also noted that users predominantly seek information that aligns with their pre-existing views, a behavior indicative of confirmation bias. This tendency shapes their interactions with media and the assessment of source credibility. The study underscores the need for further exploration into how these accounts play a supportive role in helping users navigate through their states of cognitive dissonance.